Exploring female students' perceptions of the use of digital technologies in managing academic stress - Lukenga, Maria-Pascale; Billonnet, Laurent; Gaugue, Justine; Denis, Jennifer (Frontiers in Psychology, 2023)
The purpose of this research is to explore the perceptions of female students regarding the implementation of digital technologies for academic stress management. We aim to determine if the contribution of these technologies could offer to female students a better management of the stress related to their studies and thus, a better deployment of strategies to cope with academic difficulties. A qualitative study using the focus group methodology was conducted. Our inductive and exploratory approach allowed us to focus on the experience and perception of eleven female students from the University of Mons. The cohort was divided into two groups according to their score on the Perceived Stress Scale-10 (Cohen et al., 1983). The data collected was analyzed using the thematic analysis of Braun and Clarke (2006) which allowed us to identify fourteen sub-themes divided into three axes: coping strategies used to manage academic stress, students' needs to improve their management of academic stress, and the implementation of technology for managing academic stress. Our results show that the issues present in the academic context lead students to use various coping strategies, some of which are harmful to their physical and mental health. The implementation of digital technologies and biofeedback seems to be an approach that could help students adopt more functional coping strategies and alleviate their daily difficulties in managing academic stress.